Meningkatkan Hasil Tomat dengan Trichokompos dan NPK (Studi Varietas Gustavi F1) - Noviana Noviana; Sri Ritawati; Imas Rohmawati; Dewi Firnia (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2024)
The research aimed to enhance tomato (Solanum lycopersicum L.) yield with trichocompost and NPK fertilizer: a study on Gustavi F1. This research will be conducted in Babakan Sompok village, Cimanuk District, Pandeglang City, Banten Province, from January - May 2024. This research used a factorial RCBD (Randomized Completely Block Design) consisting of 2 factors and three replications. The 1st factor was the doses of trichocompost (T), which consisted of 4 levels, namely T0 = 0 gram/polybag, T1 = 150 gram/polybag, T2 = 200 gram/polybag, and T3 = 250 gram/polybag. The 2nd factor was the doses of NPK (P), which consisted of three levels, namely P0 = 0 gram/polybag, P1 = 5 gram/polybag, P2 = 10 gram/polybag, and there are 12 treatments (repeated three times), so there are 36 experimental units and consist of 2 plants, so there are 72 plants. Data analysis for this research used the Dsaastat software. The observation parameters were the height of the plant, stem diameter, number of tomato plant leaves, age of tomato plant flower, age of harvesting tomato plant, number of fruit per plant, and weight of tomato plant fruits. The result showed that goat manure trichocompost significantly affects plant height, stem diameter, number of tomato plant leaves, and weight of tomato plant fruit. NPK fertilizer significantly affects plant height, stem diameter, number of tomato plant leaves, and weight of tomato plant fruit. There was an interaction dose of 200 gram/polybag goat manure trichocompost with a dose of 10 gram/polybag NPK fertilizer to the parameters of the number and weight of tomato plant fruits.